Analisis Keabsahan Suatu Kontrak Menurut Sistem Hukum Civil Law dan Common Law - Ruri Rifana; Ananda Sabina Zahira; Manisha Ramadanni (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Contracts and agreements are two different things. This is because a contract is basically one type of agreement. However, not all agreements reach the level of a legally binding and enforceable contract. As the problems that will be discussed in this paper are the terms of the agreement in the Indonesian civil law legal system and the terms of the contract in the English common law legal system. In Indonesia, the validity of a contract consists of four conditions, namely the agreement of those who bind themselves, the ability to make an agreement, a certain matter, and a halal or permissible cause. Meanwhile, in English there are five conditions, namely agreement (offer and acceptance, intention to create legal relations, and genuineness of consent), capacity, consideration, legal purpose, and form of contract. Based on this, the author analyzes the comparison of the validity of an agreement or contract between Indonesia and the English and its implementation. Then for the research method used is the normative legal approach method which places the law as a norm system building. The results of the research obtained are that there are significant differences in the requirements regarding the validity of an agreement or contract between Indonesian law and English law, although each of these requirements also has similarities and differences in its provisions.